Pengaruh Sistem Akuntansi dan Kompetensi Akuntansi Terhadap Potensi Penyalahgunaan Dana Desa (Studi Kasus Di Kabupaten Demak) - Husnurrosyidah, Husnurrosyidah; Suendro, Ginanjar (IAIN Kudus, 2018)
The potential for misuse of the funds of the village in Indonesia has increased due to misconstrued one side, basic education is the head of the village and its officials not derived from competencies of accounting. The village chief has the desire and the hope that created a computerized accounting system to simplify financial reporting the village Fund. Thus, a good Accounting System in conducting employee administration finance village Fund will be able to reduce the potential for abuse of the village Fund.This research aims to know the influence of the accounting system and accounting competency against the potential misuse of funds. This research is the research field (field research) with a quantitative approach. The data used are the primary data with survey methods through the dissemination of the questionnaire. There are two independent variables in this study i.e. (X 1) accounting systems and accounting competency (x 2). The dependent variable (Y) village Fund abuse. The technique of sampling using random sampling so that the retrieved samples of the 101 people who represent their respective villages in Kabupaten Demak.The results showed that 1) influential accounting systems against misuse of funds i.e. village of 0762 with p-value < 0.01; 2) influential accounting competency against the misappropriation of funds of the village i.e. of 0461 with p-value = 0.07.